Investigation of Aggression Levels of Secondary School Students Studying in Public and Private Schools, Playing and Non-Sports - İbrahim Bozkurt; Ayşegül Çelik (Türk Spor ve Egzersiz Dergisi)
This study was conducted to determine the aggression levels of secondary school students studying in public and private schools with various sub-dimensions. While the secondary education institutions in Konya constitute the universe of the research, the sample group consisted of a total of 1200 students, 600 male and 600 female, studying in 6 private and 9 state secondary education institutions located in the central districts of Konya. The schools where we conduct our study are secondary education institutions with the status of science high school, anatolian high school, sports high school and vocational high school. Personal information form was used for the socio-demographic information of the students, and the aggression inventory consisting of 30 items and the reliability of which was developed by İpek İlter KiPER was used to determine the aggression levels.For our study, Cronbach's Alpha value was determined as 0.87 for all of the items in the aggression inventory, while the Cronbach's Alpha value was determined as 0.81 for the Destructive aggression sub-dimension, 0.80 for the Assertiveness sub-dimension, and 0.79 for the Passive Aggression sub-dimension. In the examinations made, statistically significant differences were observed between the groups according to school types, gender, grade level and age. As a result; It has been observed that students studying in private schools are more aggressive than students studying in public schools. In general, it was concluded that while assertiveness and destructive aggression were high in the groups, passive aggression was low. In summary, it can be said that sports increase assertiveness and destructive aggression and decrease passive aggression.